Coblation versus dissection tonsillectomy in children - Tahyr, Sermed Ebdollatif; Yaseen, Moyaser Abdul-Rahman (Zanco Journal of Medical Sciences (ZJMS), 2018)
Background and objective: Tonsillectomy is the surgical procedure of removing the tonsils. Various methods of tonsillectomy have been practiced aimed at decreasing or eliminating intraoperative and postoperative morbidity. This study was conducted to determine the different outcomes of tonsillectomy surgery in both coblation and dissection techniques. Methods: A prospective control study was conducted with a total sample size of 66 patients. Each patient underwent tonsillectomy by using ArthroCare Coblator on the right side and dissection method on the left side. Children between the age of 3-12 years old were selected with indications of recurrent tonsillitis and/or kissing tonsil causing snoring and/or sleep apnea. Children with peritonsillar abscess, malignancy, bleeding disorder were excluded. Operative time and blood loss, postoperative pain, bleeding and healing process were compared between two methods. Operations performed by the same surgeon. Results: The intraoperative time was significantly shorter (P <0.001) and intraoperative blood loss was significantly lesser (P <00.01) in coblation as compared to dissection tonsillectomy, while there were no significant differences in the postoperative pain scores on 1st, 2nd, 7th and 14th postoperative days. There was a significant healing process in tonsillar fossa in favor of coblation rather than dissection. No primary or secondary postoperative bleeding was reported. Conclusion: Coblation tonsillectomy is a safe procedure with significantly less intraoperative time and less blood loss and better surgical wound healing with similar postoperative pain in comparison with dissection tonsillectomy.